Retraction: A reduction state potentiates the glucocorticoid response through receptor protein stabilization. (December 2013) - Kitagawa, Hirochika; Yamaoka, Ikuko; Akimoto, Chihiro; Kase, Ikuko; Mezaki, Yoshihiro; Shimizu, Takafumi; Kato, Shigeaki
<x xml:space="preserve">Abstract</x> Retraction: The above article in Genes to Cells (doi: 10.1111/j.1365‐2443.2007.01131.x ), published online on 2 November 2007 in Wiley Online Library (http://onlinelibrary.wiley.com/), has been retracted by agreement between the authors, the journal Editor in Chief, Mitsuhiro Yanagida, and Wiley Publishing Asia Pty Ltd. The retraction has been agreed to due to lack of the gel images for the lanes 1, 2, 5, 6, 9 and 10 of 'GR' and lanes 1, 2, 9 and 10 of 'Brg‐1' in Figure 3(D) and the multiple usage of the gel images in Figure 3(B) and (C).